SYNERGISM TEST OF DATE (PHOENIX DACTYLIFERA L.) AND RAW TEMPE ON ANTIOXIDANT ACTIVITY (STIKes Mitra Keluarga, 2021)
Introduction: Dates and tempeh are foods that both contain antioxidant compounds. Antioxidant compounds such as flavonoids and isoflavones are known to be found in dates and tempeh. This study was conducted to see how much antioxidant activity contained in dates and tempeh and how the effect of dates and tempeh consumed simultaneously on the increase in total antioxidant activity. Method: This study uses a direct experimental design with prospective data collection. The selected samples were dates with the type of sukkari and tempeh wrapped in plastic. Data processing was carried out using a simple linear regression statistical method. Results: The DPPH test method with UV-Visible Spectrophotometry instrument showed the results of the % inhibition value of dates fruit of 39.99% and tempeh of 24.52%. Testing the synergistic effect using 7 treatments showed that the treatment with a ratio of 50:50 had a higher % inhibition value than the other treatments, which showed that consuming dates and tempeh in a ratio of 50:50 could provide a synergistic effect on antioxidant activity. Conclusion The results obtained indicate that both samples, both dates and tempeh have high antioxidant activity, consuming both simultaneously can increase antioxidant activity. So it can be concluded that there is an effect on the synergistic effect of antioxidant activity of dates and tempeh which are consumed simultaneously. It is recommended to conduct research on the antioxidant activity of dates and tempeh using other test methods, and further research on the formulation of the preparation or clinical trials using mice.